KUALITAS PELAYANAN PUBLIK - Selvi Rianti, Zaili Rusli, Febri Yuliani (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Quality of Public Services. This study aims to determine and analyze the quality ofpublic services in the Office of Population and Civil Registry of Pelalawan Regency. This type ofresearch is a descriptive study with a qualitative approach. The informants in this study wereemployees who served and the people served. The results of the study concluded that the tangibledimensions that have indicators of appearance, comfort, convenience, and use of assistive deviceshave been applied, but there are indicators that have not been fully implemented, namely regardingthe convenience of service places. The reliability dimension which has indicators of accuracy,clear service standards, abilities, and expertise has been applied, but there are indicators that havenot worked as expected by the community, namely regarding employee expertise in using serviceaids. The dimension of responsiveness which has indicators responding, fast, precise, careful,timely and responding to complaints from service users has been implemented, this dimension is inaccordance with the wishes of the community proven because there are no complaints from serviceusers regarding indicators in the dimension of responsiviness. The assurance dimension that hasindicators of timely guarantees and guarantees of cost certainty has been implemented inaccordance with the wishes of the community. This is proven because there are no complaintsfrom service users regarding indicators in the assurance dimension. The empathy dimension thathas an indicator of prioritizing the interests of service users, friendly manners, non-discriminatory,and respectful has been implemented, but there are indicators that have not been running accordingto the expectations of the public namely regarding the unfriendliness of service employees inserving service users. The inhibiting factors for the implementation of public services in theDepartment of Population and Civil Registry of Pelalawan Regency are the lack of employeeresources and the lack of infrastructure.